In vitro antimicrosporidial activity of gold nanoparticles against Heterosporis saurida. Issue 1 (December 2016) - Saleh, Mona; Kumar, Gokhlesh; Abdel-Baki, Abdel-Azeem; Al-Quraishy, Saleh; El-Matbouli, Mansour
Abstract Background Worldwide, there is a need to expand the number of drugs available to treat parasitic infections in aquaculture. One of the new materials being tested is metal nanoparticles, which have unique chemical and physical characteristics owing to their extremely small size and high surface area to volume ratio. We examined the effectiveness of gold nanoparticles against the microsporidian parasiteHeterosporis saurida, which causes severe economic losses in lizard fish, Saurida undosquamis aquaculture. Results We synthesized gold nanoparticles by chemical reduction of tetrachloroauric acid as a metal precursor. We assessed the antimicrosporidial efficacy of the nanoparticles againstH. saurida using an in vitro screening approach, which we had developed previously using the eel kidney cell line EK-1. The number ofH. saurida spores produced in EK-1 cells was reduced in a proportional manner to the dosage of gold nanoparticles administered. A cell metabolic activity test (MTT) indicated that the gold nanoparticles did not appear to be toxic to the host cells. Conclusions Gold nanoparticles can act as an effective antimicrosporidial agent and hold promise to reduce disease in lizardfish aquaculture. Metal nanoparticles should be considered as an alternate choice for development of new antimicrosporidial drugs to combat disease problems in aquaculture.